ANALISIS RESPON GURU TERHADAP PELATIHAN PENGELOLAAN EMOSI ANAK USIA DINI - Tien Asmara Palintan (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2020)
The problem of managing emotions in early childhood that the researchers found was that early childhood teachers found it difficult to develop the emotional aspects of children. Early Childhood Emotion Management Training is used as an intervention in helping PAUD teachers to develop emotional aspects of early childhood. The subjects in this training consisted of 31 PAUD teachers. This study refers to an experimental approach with the One-Shot Case Study design. Subjects were given treatment in the form of Early Childhood Emotion Management Training and then the results were observed. This training was held three times, with a duration of 120 minutes for each meeting. Validation of the Teacher Response Questionnaire (ARG) obtained a value of = 3.64, including the very valid category. The empirical validation of the study stated that 98% of research subjects stated that the teacher's response was very good (positive) towards the implementation of early childhood emotional management training.